2015 Social Accounting Matrix for Tunisia - Institut Tunisien de la Compétitivité et des Etudes Quantitatives; International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The Tunisian regionalized SAM is built using the national accounts statistics, the Supply and Use Tables for 2015 that were produced by National Institute of Statistics (NIS). The regionalized matrix is constructed in three steps that are national, household and regional. The national 2015 SAM for Tunisia includes 46 sectors and 46 products. For the household SAM, factors of production and the household accounts are split, respectively into 13 and 15 factor and household categories. Labor is disaggregated across rural and urban areas and into four education-level categories. Capital is also disaggregated into four subcategories: crops, livestock, mining, and other; and land. Households are disaggregated by national per capita expenditure quintiles, and then split into rural farm, rural nonfarm, and urban households. For the regionalized SAM, sectoral production, production factors, and household groups are disaggregated into seven subnational regions: Greater Tunis, North East, North West, Center East, Center West, South East and South West. In total, the regional 2015 SAM includes 105 household groups and composed of 513 rows x 513 columns.